Der Arzt als Agent des Patienten: Zur Übertragbarkeit der Principal-Agent-Theorie auf die Arzt-Patient-Beziehung - Udo Schneider (Universität Greifswald, Rechts- und Staatswissenschaftliche Fakultät, 1998)
– The paper presents a principal-agent model to analyse the relationship between physicians and patients. The application of the standard principal-agent model shows some shortcomings of the analysis when being implemented into the field of health economics. Therefore it is necessary to look at the interactions and incentives between the three major players in health care: physicians, patients and sickness funds. The central point is that the key players (physicians, patients and sickness funds) together determine health care expenditure and the stock of health capital. Here, a theoretical model of the physician-patient relationship has to consider further participants as well as their interactions.
Keywords: 330